Discrepancy between ELISPOT IFN-γ secretion and binding of A2/peptide multimers to TCR reveals interclonal dissociation of CTL effector function from TCR-peptide/MHC complexes half-life - Rubio-Godoy, Verena (The National Academy of Sciences, 2001)
Activation of CD8(+) cytolytic T lymphocytes (CTLs) by antigen is triggered by the interaction of clonotypic αβ T cell receptors (TCRs) with antigenic peptides bound to MHC class I molecules (pMHC complexes). Fluorescent multimeric pMHC complexes have been shown to specifically stain antigen-specific CTLs by directly binding the TCR. In tumor-infiltrating lymphocytes from a melanoma patient we found a high frequency of tyrosinase(368–376) peptide-specific cells as detected by IFN-γ ELISPOT, without detectable staining with the corresponding A2/peptide multimers. Surprisingly, these T cells were able to lyse tyrosinase(368–376) peptide-pulsed target cells as efficiently as other specific T cells that were stained by multimers. Analysis of the staining patterns under different conditions of incubation time and temperature revealed that these results were explained by major differences in TCR-multimeric ligand interaction kinetics among the clones. Whereas no direct quantitative correlation between antigenic peptide concentration required for CTL effector functions and equilibrium multimer binding was observed interclonally, the latter was profoundly affected by the kinetics of TCR-ligand interaction. More importantly, our data indicate that similar levels of T cell activation can be achieved by independent CD8(+) T cell clonotypes displaying different TCR/pMHC complex dissociation rates.